Hybrid tool-1: Google Meet attendance list (OWL) via extension Chrome / Nor Hanim Abd Rahman - Abd Rahman, Nor Hanim (Unit Penerbitan dan Publisiti JSKM, 2022)
Are you having trouble keeping track of the students' attendance when having online revisions or lecturing sessions? Or, when online meeting among colleagues? Perhaps, you are just looking for another alternative of keeping track? Then why not try this option or extension from Chrome. It is free and user-friendly.